ANALYSIS OF ORGANOLEPTIC PARAMETERS AND HEAVY METALS IN ARTIFICIALLY RIPENED MANGO FRUITS IN PAKISTAN. - S. Abbas; B. J. Azhar; M. Irfan; S. Ahmad; I. Ahmed; J. Hussain; S. N. Shakeel; 4 (Journal of Animal and Plant Sciences, 2020)
Calcium carbide (CaC2)is still commonly used as artificial fruit ripening agent for mangoes in many developing countries like Pakistan despite of the major concern of arsenic (As) and other metals contaminations. We used Particle Induced X-ray Emission (PIXE) for the detection of arsenic traces in commercially availableCaC2andartificially ripened mangoes (ARM). Presence of harmful arsenic residues in calcium carbide (CaC2) treated fruits provided evidences that arsenic traces were transferred from calcium carbide (CaC2) which is used for ripening. Mature green mangoes were treated with CaC2in three different ways (T1- T3) and were compared to fully ripened mangoes bought from local markets (T4) and non-treated mangoes (T0). Pulverized mango samples were irradiated by 3MeV collimated protons from 5MV tandem accelerator at National Institute of Physics, Pakistan and emitted X-ray spectrum was analyzed using GUPIXWIN to detect significant amount of As traces with differential presence of several other elements. Arsenic presence was further validated and endorsed in mango fruits using Graphite Furnace Atomic Absorption Spectrometry (GFAAS) and Inductivity Coupled Plasma Mass Spectrometry (ICP-MS). Absence of As traces in non-treated control mangoes has provided evidence of As contamination in artificially ripened mangoes is associated with CaC2 used for ripening. Arsenic residues in CaC2 treated mangoes can easily added up to already available arsenic exposure towards the limits shown for several cancerous diseases. Present study will not only provide a direct method of arsenic detection in fruits, but also suggest the need of strict implementations and improvements in the existing food safety rules and regulations to completely ban this carcinogenic chemical for its future applications.
Keywords: PIXE; Arsenic; Hazardous; Calcium Carbide; Post harvest